Panel‐based next‐generation sequencing identifies novel mutations in Bulgarian patients with inherited retinal dystrophies. Issue 8 (3rd June 2022) - Kamenarova, Kunka; Mihova, Kalina; Veleva, Nevyana; Mermeklieva, Elena; Mihaylova, Bilyana; Dimitrova, Galina; Oscar, Alexander; Shandurkov, Iliyan; Cherninkova, Sylvia; Kaneva, Radka
Abstract: Background: Next‐generation sequencing (NGS)‐based method is being used broadly for genetic testing especially for clinically and genetically heterogeneous disorders, such as inherited retinal degenerations (IRDs) but still not routinely used for molecular diagnostics in Bulgaria. Consequently, the purpose of this study was to evaluate the effectiveness of a molecular diagnostic approach, based on targeted NGS for the identification of the disease‐causing mutations in 16 Bulgarian patients with different IRDs. Methods: We applied a customized NGS panel, including 125 genes associated with retinal and other eye diseases to the patients with hereditary retinopathies. Results: Systematic filtering approach coupled with copy number variation analysis and segregation study lead to the identification of 16 pathogenic and likely pathogenic variants in 12/16 (75%) of IRD patients, 2 of which novel (12.5%): ABCA4‐ c.668delA (p.K223Rfs18) and RР1‐ c.2015dupA (p.K673Efs*25). Mutations in the ABCA4, PRPH2, USH2A, BEST1, RР1, CDHR1, and RHO genes were detected reaching a diagnostic yield between 42.9% for Retinitis pigmentosa cases and 100% for macular degeneration, Usher syndrome, and cone‐rod dystrophy patients. Conclusion: Our results confirm the usefulness of targeted NGS approach based on frequently mutated genes as a comprehensive and successful genetic diagnostic tool for IRDs with significant impact on patients counseling. Abstract : Our data reports the results from application of a custom NGS panel, including common genes associated with retinal and other eye diseases for genetic characterization 16 Bulgarian patients with hereditary retinopathies. A total of 16 pathogenic and likely pathogenic variants, 2 of which novel were found in 75% of patients. Mutations in the ABCA4, PRPH2, USH2A, BEST1, RР1, CDHR1 and RHO genes were identified. The achieved detection rate confirms the usefulness of targeted NGS approach based on frequently mutated genes as a comprehensive and successful genetic diagnostic tool for inherited retinal degenerations.